POLITICAL LEGAL POLICY THROUGH THE IMPLEMENTATION OF RESTORATIVE JUSTICE IN RENEWAL CRIMINAL LAW - Heru Suhendro; Syaiful Asmi Hasibuan (PT. Radja Intercontinental Publishing, 2023)
Criminal law policy is one form of law, in terms of restorative justice it is an alternative for resolving cases outside of court (non-litigation). The aim of this research is to find legal political options in criminal law reform. Using a juridical approach using secondary data, it can be concluded that the legal politics of criminal law reform in Indonesia is currently still ongoing and is part of the development of the national legal system. The legal politics of developing a national legal system must be based on Pancasila as a guide and filtering tool for national legal politics and the 1945 Constitution as the basic law. One form of political reform of criminal law is to adopt the concept of restorative justice as an alternative mechanism for resolving legal problems that occur without using the judicial process. With this restorative justice approach, law enforcement from having always used a retributive (retaliation) approach has shifted to a restorative (recovery) approach. The concept of restorative justice can become a permanent legal policy in building the future national criminal law system.